Interest in a Twitter-delivered weight loss program among women of childbearing age. Issue 2 (30th December 2015) - Waring, Molly E.; Schneider, Kristin L.; Appelhans, Bradley M.; Simas, Tiffany A. Moore; Xiao, Rui S.; Whited, Matthew C.; Busch, Andrew M.; Evans, Martinus M.; Pagoto, Sherry L.
Abstract: Weight management through the childbearing years is important, yet few women have access to efficacious weight loss programs. Online social network-delivered programs may increase reach and thus impact. The aim of this study was to gauge interest in a Twitter-based weight loss intervention among women of childbearing age and the feasibility of recruitment via Twitter. We recruited English-speaking women aged 18–45 years ( N  = 63) from Twitter to complete an anonymous online survey including open-ended questions about program advantages and concerns. Forty percent of participants were obese and 83 % were trying to lose weight. Eighty-one percent were interested in a Twitter-delivered weight loss program. Interest was high in all subgroups (62–100 %). Participants (59 %) cited program advantages, including convenience, support/accountability, and privacy. Concerns (59 %) included questions about privacy, support/accountability, engagement, efficacy, and technology barriers. Research is needed to develop and evaluate social media-delivered interventions, and to develop methods for recruiting participants directly from Twitter.